WCET®'s International Ostomy Guideline: survey of stakeholder priorities. - Haesler, Emily; Ayello, Elizabeth A.; Chabal, Laurent O.; Hibbert, Denise; Prentice, Jennifer L.; Costa Pereira, Joaquim; Nunoo-Mensah, Joseph W.; Atkinson, Julie; McNair, Richard (World Council of Enterostomal Therapists Journal, 2025)
Aim The aim of this survey was to ensure that the World Council of Enterostomal Therapists® (WCET®) International Ostomy Guideline (IOG) 3rd Edition considers stakeholder interest in the clinical questions posed. Methods Ostomates, surgeons and nurses specialising in stoma care globally were surveyed on the importance of the clinical questions developed by the IOG-Guideline Development Panel (IOG-GDP). An online survey was distributed to committee members of the WCET®, the International Society of University of Colon and Rectal Surgeons (ISUCRS) and the International Ostomy Association (IOA). The anonymous survey was available for four weeks online. Data on stakeholder demographics and their level of interest in 31 proposed clinical questions was collected. The level of interest in each question was measured using a 5-point Likert scale. Additional information was elicited by openended questions. Descriptive statistics were used to analyse answers to the Likert-style questions, and open-response questions were analysed by grouping responses in general themes. Results Responses (n=103) were received from members of/aligned with ISUCRS (n=37) or 29 the WCET® (n=29), people living with a stoma and/or an informal caregiver (n=10), and individuals not indicating an affiliation (n=27). Respondents expressed a high level of interest in all proposed questions. Level of positive interest in quality of life questions ranged from 97.96% to 87.38%. For individual's knowledge, skills and self-care positive interest ranged from 88.35% to 93.20%; health professionals' questions were all above 85%; preoperative care ranged from 88.35% to 94.18%; postoperative care ranged from 88.35% to 94.99%; products above 90%; ongoing/long-term care ranged from 85.44% to 93.2%. For questions on specific populations, the level of positive interest in religious/cultural considerations was 82.53%; populations with specific needs ranged from 76.70% for individuals at the end of live to 91.26% for individuals who are over/under weight or with obesity. Suggestions on additional topics and resources were generally unique. Conclusion There is a high level of interest in the clinical questions developed by the IOG-GDP, indicating nurses, surgeons and individuals living with a stoma have very similar expectations about guideline content.